Oleanolic acid rescues critical features of umbilical vein endothelial cells permanently affected by hyperglycemia - Stelling-Férez, Javier; Cappellacci, Ilaria; Pandolfi, Assunta; Gabaldón, José Antonio; Pipino, Caterina; Nicolás, Francisco José (Frontiers in Endocrinology, 2023)
Skin wound healing is a physiological process that involves several cell types. Among them, endothelial cells are required for inflammation resolution and neo-angiogenesis, both necessary for tissue restoration after injury. Primary human umbilical vein endothelial cells (C-HUVECs) are derived from the umbilical cord. When women develop gestational diabetes, chronic exposure to hyperglycemia induces epigenetic modifications in these cells (GD-HUVECs) leading to a permanent pro-inflammatory phenotype and impaired angiogenesis in contrast to control cells. Oleanolic acid (OA) is a bioactive triterpenoid known for its epithelial cell migration promotion stimulation and higher tensile strength of wounds. However, the potentially anti-inflammatory and pro-angiogenic properties of OA are still under investigation. We tested OA on C-and GD-HUVECs under inflammatory conditions induced by low levels of the inflammatory cytokine TNFα. Reduced expression of adhesion molecules VCAM1, ICAM1, and SELE was obtained in OA-pre-treated C-and GD-HUVEC. Additionally, protein VCAM1 levels were also decreased by OA. Coherently, monocyte adhesion assays showed that a lower number of monocytes adhered to GD-HUVEC endothelium under OA pre-treatment when compared to untreated ones. It is noteworthy that OA improved angiogenesis parameters in both phenotypes, being especially remarkable in the case of GD-HUVECs, since OA strongly rescued their poor tube formation behavior. Moreover, endothelial cell migration was improved in C-and GD-HUVECs in scratch assays, an effect that was further confirmed by focal adhesion (FA) remodeling, revealed by paxillin staining on immunocytochemistry assays. Altogether, these results suggest that OA could be an emergent wound healing agent, due to its capacity to rescue endothelial malfunction caused by hyperglycemia.